(untitled) (REMUNOM, 2026)
Access to justice constitutes one of the fundamental pillars of the Democratic Rule of Law, as it is essential for guaranteeing and enforcing fundamental rights. However, several institutional, social and technological factors still represent significant challenges to the effective realization of this right in the Brazilian context. In this perspective, the present study aims to analyze access to justice as a fundamental right and to discuss the main challenges related to its effective implementation in Brazil. The research was conducted through a qualitative literature review based on the analysis of recent scientific articles published in academic legal journals. The selection of sources considered criteria such as relevance to the topic, recency of publication and scientific quality. The results indicate that the effectiveness of access to justice depends on the articulation of different institutional strategies, including the strengthening of legal institutions, the adoption of alternative dispute resolution mechanisms and the incorporation of digital technologies into the judicial system. The analysis also demonstrates that overcoming structural barriers that restrict citizens’ access to the justice system requires the implementation of public policies aimed at social inclusion and institutional efficiency. It is concluded that the development of a more accessible, efficient and inclusive justice system represents a fundamental step toward strengthening democratic institutions and ensuring the effective protection of fundamental rights.